Association between auditor attributes and audit lag - Tay, Shu Jia (2008)
We investigate the association between various client-perceived auditor attributes and audit lag (defined as the number of calendar days from the fiscal year end to the audit report date) based on a sample of 250 Singapore companies. The findings suggest: (1) auditor attributes potentially affect audit lag, and (2) a trade-off might exist between audit quality and audit lag.